Romeo + Juliet - Luhrmann, Baz; DiCaprio, Leonardo; Danes, Claire, 1979-; Shakespeare, William, 1564-1616. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2002)
The classic story of star-crossed lovers, set in a futuristic urban Verona Beach.
Features: audio commentary, cinematographer's gallery: scene studies with Don McAlpine, director's gallery: go behind the scenes with Baz Luhrmann, cast and crew interviews, design gallery: production stills narrated by Catherine Martin, music videos "Young hearts run free," and "Kissing you," DVD-ROM screenplay comparison excerpts, theatrical trailer, TV spots and more.
Leonard DiCaprio, Claire Danes, Brian Dennehy, John Leguizamo, Pete Postlethwaite, Paul Sorvino, Diane Venora.
MPAA rating: PG-13.
DVD, Dolby digital 5.1 surround.
In English or French with optional English or Spanish subtitles.
Keywords: Romeo (Fictitious character) -- Drama; Juliet (Fictitious character) -- Drama; Vendetta -- Drama; Video recordings for hard of hearing people; Based on the book; Feature films